Clinical Efficacy of Bacillus Clausii Probiotic in the Management of Acute Diarrhoea in Children - Hamid, Farzana; Quaium, Syed Moosa MA; Rahman, Azizur; Hussain, Tania; Islam, Tahi MD Tahmid (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2019)
Background: Diarrhoea is the second most common cause of under five mortality especially in developing world. Very few studies have been conducted so far on bacillus clausii probiotic with inconsistent result. So, the aim of the present study is to determine the clinical efficacy of Bacillus Clausii probiotic formulation as adjunct treatment of acute diarrhoea. Materials and methods: This prospective single blind randomized controlled trial included 310 infants and children between 6 months to 6 years of age admitted in a tertiary care hospital Sylhet, Bangladesh with acute watery diarrhoea having varied dehydration status ranging from no to severe dehydration excluding shocked state. Cases were randomly assigned to two groups: Group A (n=150) comprised of children who were treated with standard treatment (According to WHO guideline) only as control group and Group B who received standard treatment plus Bacillus Clausii as probiotic. Clinical responses were evaluated in terms of improvement of outcome variables such as duration and frequency of diarrhoea and duration of hospital stay. Results: Mean duration of diarrhoea was 3.3(±1.1) days in Group A and 3.2(±1.3) days in Group B which was not statistically significant. Frequency of diarrhoea decreased significantly at day 4 of treatment in both study groups showing no statistical difference. Mean duration of hospital stay in both groups was 3.8 days showing no significance. Conclusion: Bacillus Clausii is ineffective in reducing the duration, frequency of diarrhoea and duration of hospital stay. Chatt Maa Shi Hosp Med Coll J; Vol.18 (1); Jan 2019; Page 14-17